Bipolarna motnja razpoloženja - Frangeš, Tadeja (Medicinski razgledi, 2013)
Bipolar disorder is very prevalent in general population. According to Diagnostic and statistical manual ofmental disorders, fourth revision - DSM-IV, four types ofbipolar disorder are distinguished: bipolar disorder 1, bipolar disorder II, cyclothymia, and other types (not specified otherwise). Etiology of disorder is multifactorial with overlap between genetic, environmental"and neurobiological factors. Due to complexity of clinical features it represents diagnostical and therapeutical challenge to clinicians. Treatment of bipolar disorder demands multidisciplinary approach and consists of pharmacotherapy, psychotherapy, psychoeducation and sociotherapy. Pharmacotherapy includes mood stabilizers, antidepressants, anxiolytics, and antipsychotics. Due to frequent comorbidity with anxiety disorders, possible suicidality and other complications that is intrinsic to disease the choice and combination of medications is crucial. This is especially important in order to achieve long term and stable remissions in patients with bipolar disorder.
Keywords: bipolar disorder; bipolarna motnja; depresija; depression; mania; manija